Organic Matter, Nutrients and Trace Metals of Serin River - Ling, Teck Yee; Srikaran, Rohene; Kho, Chui-Ping; L., Nyanti (IDOSI Publication, 2010)
Animal and fish farming may lead to water quality deterioration. Water quality of the Serin River was assessed at seven selected stations over six sampling trips. The tributary with animal farm discharge had the lowest DO (2.2 mg/L), highest BOD, phosphorus (P), ammonia-nitrogen (TAN), organic-nitrogen (org-N), TKN and Cu and second highest in nitrate-nitrogen (NO)-N) and Ni. The station with fish culture recorded the highestNi, Cd and DO (5 mg/L) and third highest in Inorg-P, Org-P and Pb. Near the village and school, Cr was the highest and Org-P was second highest. Stations by the road and bridge recorded the highest zinc, lead and second highest in copper attributable to vehicles. Downstream of animal farm discharge with discarded e-waste, old tires and glass also recorded high Zn, Pb and Cd. The station near crop farming showed highest NO-N, second highest in BOD, lnorg-P, TAN and Ni and third in Cd and Cr attributable in inorganic fertilizers. Trace metals complied with the USA drinking water criteria except Cd at the tributary receiving animal farm effluent and Pb at all stations. Principal component analysis showed classification of heavy metals according to sources. Effluent from animal and fish farms need to be treated, solid waste need to be recycled and stormwater need to be treated to protect the water quality of the river.